Post-transplant donor-specific anti-HLA antibodies with a higher mean fluorescence intensity are associated with graft fibrosis in pediatric living donor liver transplantation - Goto, Ryoichi; Fukasaku, Yasutomo; Ganchiku, Yoshikazu; Kawamura, Norio; Watanabe, Masaaki; Ota, Takuji; Hatanaka, Kanako C.; Suzuki, Tomomi; Shimamura, Tsuyoshi; Taketomi, Akinobu (Frontiers in Pediatrics, 2023)
The roles of post-transplant anti-HLA donor specific antibody (DSA) in pediatric liver transplantation (LT), including therapeutic strategies, remain controversial. This study aimed to identify the risks of post-transplant DSA for graft fibrosis progression in pediatric living donor LT (LDLT). We retrospectively evaluated 88 LDLT pediatric cases between December 1995 and November 2019. DSAs were assessed with single antigen bead test. Graft fibrosis was histopathologically scored with METAVIR and the centrilobular sinusoidal fibrosis system. Post-transplant DSAs were detected in 37 (52.9%) cases at 10.8 (1.3-26.9) years post-LDLT. The histopathological examination of 32 pediatric cases with post-transplant DSA revealed that 7 (21.9%) with a high DSA-MFI (≥9378) showed graft fibrosis progression (≥F2). No graft fibrosis was observed in the subjects with a low DSA-MFI. The risk factors for developing graft fibrosis in pediatric cases with post-transplant DSA were an older graft age (>46.5 years old), lower platelet count (<10.7×104/ml) and higher Fib4 index (>0.7807, recipient age; >1.8952, donor age). Limited efficacy of additional immunosuppressants was observed in DSA positive pediatric cases. In conclusion, pediatric cases with a high DSA-MFI and risk factors should undergo a histological examination. The appropriate treatment for post-transplant DSA in pediatric LT needs to be determined.